Dvosmerna avdiovizualna komunikacija na stalni razstavi SEM - Valentinčič Furlan, Nadja (Etnolog. Nova vrsta (Ljubljana), 2013)
The author reports how two-way audiovisual communication develops in the second permanent exhibition I, we and the others: images of my world in the Slovene Ethnographic Museum (SEM). It is triggered by the mosaic portrait Vesna, which shows how we can identify the exhibition's contents in the life of a young Slovene woman, and also invites the visitors to film a portrait of a close relative or a self-portrait. The museum also offers the visitors an easier option: to have their story filmed by the museum's team. The stories ofthe visitors and the video portraits enrich the exhibition with authentic Slovene voices and images from the everyday life of individuals and groups. They can be accessed on the interactive application Visitor Responses and the stories also feature on the SEM's website. The findings from the creation of a long-term audiovisual project as part of the museum exhibition refer to the exhibition's peripheral contents and communication channels, field filming, and the training of two voluntary culture mediators for filming personal stories, as well as to the communication with visitors and potential authors. The text also discusses the presumed democratic nature of the video medium.
Keywords: ocene in poročila; stalne razstave; ethnology; etnologija; vsakdanje življenje; avdiovizualno gradivo; avdiovizualni projekti; komunikacija